Entry regulation and competition evidence from retail and labor markets of pharmacists - Davud Rostam-Afschar; Maximiliane Unsorg (University of Tübingen, Faculty of Economics and Social Sciences, 2021)
We examine a deregulation of German pharmacists to assess its effects on retail and labor markets. From 2004 onward, the reform allowed pharmacists to expand their single-store firms and to open or acquire up to three a liated stores. This partial deregulation of multi-store prohibition reduced the cost of firm expansion substantially and provides the basis for our analysis. We develop a theoretical model that suggests that the general limitation of the total store number per firm to four is excessively restrictive. Firms with hig exteuroh managerial e ciency will open more stores per firm and have higher labor demand. Our empirical analysis uses very rich information from the administrative panel data on the universe of pharmacies from 2002 to 2009 and their a liated stores matched with survey data, which provide additional information on the characteristics of expanding firms before and after the reform. We find a sharp immediate increase in entry rates, which continues to be more than five-fold of its pre-reform level after five years for expanding firms. Expanding firms can double revenues but not profits after three years. We show that the increase of the number of employees by 50% after five years and the higher overall employment in the local markets, which increased by 40%, can be attributed to the deregulation.
urn:nbn:de:bsz:21-dspace-1154277; hdl:10900/115427
Keywords: L4; L5; L2; J44; J23; 330; regulation; acquisitions; entry; market concentration; wages; employment; pharmacists